Postawy wobec polskiej polityki historycznej: wyniki eksperymentu - Wawrzyński, Patryk; Schattkowsky, Ralph; Muszyński Gabriela Czarnek, Marek A.; Czarnek, Gabriela (Polityka i Społeczeństwo, 2021)
The paper presents the preliminary results of the interdisciplinary study on the influence of the government’s remembrance policy. The key aspect of the project was a measurement of 364 students’ attitudes towards management of collective memory in laboratory conditions. Its objective was a diagnosis of Polish youth’s disposition to the management of collective memory by a state, but also a measurement of attitude change resulting from a narrative (which imitated the remembrance policy). The paper discusses general results of the study and three aspects of attitudes: cognitive, emotional and behavioral. It presents both results from the first measurement and effects of emotions’ and commitment’s manipulation. Collected data was used to formulate four research conclusions which consider attitudes towards the government’s remembrance policy, their change and their relevance to a question on the distribution of influence between a government and a civil society.